SONOGRAPHIC EVALUATION OF OUTFLOW VEINS IN SUDANESE LIVER TRANSPLANTS - Mohammed Osman, Ashraf Mustafa; Gar al naby, Mohammed Al Fadil; Ahmed, Asma Ibrahim; Awad alla, Babiker Abd Elwahab (International Journal of Research -GRANTHAALAYAH, 2018)
The purpose of this study was to identify the specific Doppler criteria for the outflow vein (hepatic veins and inferior vena cava) obstruction in liver transplants. A case control study was done after performing venous Doppler sonographic studies in 300 normal (control) and 45 liver transplant cases (4 whole liver, 41 lobar) with no vascular obstruction. The ultrasonic Doppler study were classified as normal, occluded, or stenosed on the basis of gray scale and color flow mapping appearances as well as elevated or absent waves. The following Doppler parameters were evaluated: the outflow veins on color Doppler interrogation, venous pulsatility index on spectral trace. Receiver operating characteristic curves were constructed. There were no cases of outflow vein obstruction found in our sample (neither stenosis, nor occlusion). Mean venous pulsatility index for normal outflow veins was 0.75 and is found ranging between (0.55-0.75). A venous pulsatility index of < 0.45 is specific for stenosis (5). The venous pulsatility index is a useful parameter for diagnosing venous stenosis in liver transplants.